Combining citrulline with atorvastatin preserves glucose homeostasis in a murine model of diet‐induced obesity. (13th October 2015) - Capel, Frédéric; Chabrier, Gwladys; Pitois, Elodie; Rigaudière, Jean‐Paul; Plenier, Servane Le; Durand, Christine; Jouve, Chrystèle; de Bandt, Jean‐Pascal; Cynober, Luc; Moinard, Christophe; Morio, Béatrice
Abstract : Background and Purpose: NO is a crucial regulator of energy and lipid metabolism, whose homeostasis is compromised during obesity. Combination of citrulline and atorvastatin potentiated NO production in vitro . Here we have assessed the effects of this combination in mice with diet‐induced obesity (DIO). Experimental Approach: C57BL/6J male mice were given a standard diet (control) or a high fat–high sucrose diet (DIO) for 8 weeks. DIO mice were then treated with DIO alone, DIO with citrulline, DIO with atorvastatin or DIO with citrulline and atorvastatin (DIOcit–stat) for 3 weeks. Thereafter, body composition, glucose tolerance, insulin sensitivity and liver fat metabolism were measured. Key Results: DIOcit–stat mice showed lower body weight, fat mass and epididymal fat depots compared with other DIO groups. Unlike other DIO groups, glucose tolerance and insulin sensitivity of DIOcit–stat, along with blood glucose and insulin concentrations in response to feeding, were restored to control values. Refeeding‐induced changes in liver lipogenic activity were also reduced in DIOcit–stat mice compared with those of DIO animals. This was associated with decreased gene expression of the transcription factor SREBP‐1, liver X receptor α, ChREBP and of target lipogenic enzymes in the liver of DIOcit–stat mice compared with those of other DIO groups. Conclusions and Implications: The citrulline–atorvastatin combination prevented fat mass accumulation and maintained glucose homeostasis in DIO mice. Furthermore, it potentiated inhibition of hepatic de novo lipogenesis activity. This combination has potential for preservation of glucose homeostasis in patients receiving statin therapy.